Mapping the Evolution of Human Capital in the Age of Artificial Intelligence: A Bibliometric Analysis - AISSA Sara; REGHIOUI Anouar (Revue Internationale du Chercheur, 2025)
In the contemporary landscape of rapid technological advances, understanding the intersection between artificial intelligence (AI) and human capital development is crucial to shaping future workforce management and skills enhancement strategies. This article presents a comprehensive bibliometric analysis aimed at elucidating trends, dynamics and key contributions in this field. Drawing on a corpus of 3,591 papers ranging from seminal works to recent research findings, our analysis highlights key themes, influential authors and notable works that have shaped the discourse on AI-driven human capital evolution. The results reveal a rich trajectory of research, with a particular focus on digital marketing and social media research, highlighting the transformative potential of AI in shaping marketing practices. In addition, significant contributions emerge from studies focused on workforce development, talent management and skills enhancement, reflecting the growing recognition of AI’s impact on shaping the future workforce. Using bibliometric techniques such as co-citation analysis and keyword clustering, this study reveals six distinct clusters representing different facets of the link between AI and human capital. These clusters encompass diverse topics ranging from the implications of AI on organizational behavior to the role of education in preparing individuals for the AI-driven economy.